The value of thermal management control strategies for battery energy storage in grid decarbonization: Issues and recommendations - Hannan M.A.; Al-Shetwi A.; Begum R.A.; Young S.E.; Hoque M.M.; Ker P.; Mansur M.; Alzaareer K. (Elsevier Ltd, 2023)
Battery management systems; Carbon; Controllers; Decarbonization; Electric batteries; Electric power system control; Electric power transmission networks; Environmental impact; Gas emissions; Greenhouse gases; Industrial management; Life cycle; Renewable energy resources; Storage management; Temperature control; Thermal management (electronics); Battery energy storage; Battery thermal managements; Electricity production; Experimental validations; Issues and challenges; Power system operations; Renewable energy integrations; Renewable energy source; Battery storage